Fun at workplace and intention to leave: role of work engagement and group cohesion. Issue 2 (16th December 2021) - Jyoti, Jeevan; , Dimple
Abstract : Purpose: The purpose of this study is to examine the role of work engagement (WE) and group cohesion (GC) in the context of fun at workplace (FAW) and its outcomes. Design/methodology/approach: In total, 753 employees of fast food chain restaurants in India have been contacted, and 244 responded back. Exploratory and confirmatory factor analyses have been conducted to assess the reliability and validity of the data. Further, the hypothesized relationships have been tested using structural equation modeling. Findings: The findings of the study revealed that WE mediates the relationship between FAW and intention to leave (ITL). Further, GC moderates the relationship between FAW and WE. Research limitations/implications: This research has been conducted in fast food chain restaurants only, and the data is cross-sectional in nature. Practical implications: Organizations should develop a business culture based on fun and enjoyment, which will help in creating a comfortable environment for employees and reduce their ITL. Social implications: Society benefits a lot if employees have positive work experiences. FAW will help to reduce the negative spillover of work pressure/stress to the home. Employees will come home with minimum work stress and will contribute positively to their personal and social life. Originality/value: The present study empirically tested the mediating role of WE between FAW and ITL and moderating role of GC between FAW and WE that helped a lot to understand the relationships in the workplace setting.